1998
DOI: 10.1177/109019819802500506
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Readiness to Make Dietary Changes

Abstract: This article examines the relationship between reported social support and readiness to increase fruit and vegetable consumption, based on the Transtheoretical Stage of Change Model. Data were collected as part of the baseline assessments for a work site intervention study promoting increased consumption of fruits and vegetables. Among workers who did not live alone, household support was significantly higher for those of Hispanic and African American heritage than other groups, and was also higher among men, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Our finding that greater readiness to change portion size was related to receiving more encouragement from friends for healthy eating is consistent with an earlier study, which indicated that level of social support is associated with readiness to change dietary behaviors (Sorensen, Stoddard, & Macario, 1998). There are numerous weight loss programs, most notably Weight Watchers (Heshka et al, 2003), that are based on peer support for achieving and maintaining goals.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that greater readiness to change portion size was related to receiving more encouragement from friends for healthy eating is consistent with an earlier study, which indicated that level of social support is associated with readiness to change dietary behaviors (Sorensen, Stoddard, & Macario, 1998). There are numerous weight loss programs, most notably Weight Watchers (Heshka et al, 2003), that are based on peer support for achieving and maintaining goals.…”
Section: Discussionsupporting
confidence: 92%
“…These advisory boards were given responsibility for tailoring and implementing program activities, which led to significant increases in employees' consumption of fruit and vegetables. Additionally, social norms around eating may be positively influenced by training employees to educate their peers about good nutrition [88]. Peer educators can provide daily support for colleagues making a behavioral change and are best qualified to tailor healthy eating messages to the unique needs and culture of their coworkers [89].…”
Section: Workitesmentioning
confidence: 99%
“…Sorensen et al (1998) emphasize the importance of workplace social support in promoting health behavior change. 55 Worksite environment and social influences may improve dietary habits 56 and physical activity levels. 18,57-60 Likewise, higher perceived supervisor support might be associated with improved sleep.…”
Section: Introductionmentioning
confidence: 99%